Algorithm for identification of asthma–COPD overlap: consensus between the Spanish COPD and asthma guidelines. Issue 5 (2nd May 2017) - Miravitlles, Marc; Alvarez-Gutierrez, Francisco Javier; Calle, Myriam; Casanova, Ciro; Cosio, Borja G.; López-Viña, Antolín; Pérez de Llano, Luis; Quirce, Santiago; Roman-Rodríguez, Miguel; Soler-Cataluña, Juan José; Plaza, Vicente
It was as early as 1959 that the report of the CIBA Symposium described the possible coexistence of different obstructive airway diseases, such as asthma, chronic bronchitis and/or emphysema, in the same individual. However, because there were no specific therapies for all these different expressions of lung disease, these overlaps were largely ignored by guidelines. In 1995, the American Thoracic Society chronic obstructive pulmonary disease (COPD) statement included a Venn diagram with the different possible overlaps of clinical presentation of obstructive lung diseases [1], but no specific recommendations of treatment were provided for them. It was not until 2007 that the Canadian COPD guidelines specified that: "if the asthma component (in COPD) is prominent, earlier introduction of inhaled corticosteroids (ICS) may be justified" [2]. Later, in 2010, the Japanese guidelines for COPD dedicated a chapter to "Treatment of COPD complicated by asthma" [3]. To the best of our knowledge, the Spanish guidelines for COPD (GesEPOC) in 2012 were the first to propose specific criteria for the identification of the so-called asthma–COPD overlap (ACO) [4, 5]. Because there was no internationally accepted definition of ACO, a group of experts proposed diagnostic criteria for ACO in COPD [6] and these were adopted in the document. The major criteria were as follows: a very positive bronchodilator response (>400 mL and >15% increase in forced expiratory volume in 1 s (FEV1 )), sputum eosinophilia or a previous diagnosis of asthma. Minor criteria were an increased total serum IgE, previous history of atopy or a positive bronchodilator test (>200 mL and >12% in FEV1 ) on at least two occasions [6]. To be diagnosed with ACO, a patient must fulfil two major or one major and two minor criteria. Other national guidelines for COPD, such as the Finnish [7] and the Czech guidelines [8], followed this approach and proposed similar criteria for ACO. An algorithm to identify patients with ACO rather than asthma or COPD alone http://ow.ly/Viyy308Ehdk